Oral Hygiene Practices, Knowledge, and Self-Reported Dental and Gingival Problems with Rural-Urban Disparities among Primary School children in Lilongwe, Malawi - F. Mlenga; E. G. Mumghamba (International Journal of Dentistry)
Aim. To determine oral hygiene practices, knowledge, and experience of dental caries and gingival problems among urban and rural primary schoolchildren in Lilongwe District, Malawi. Methodology. This was an analytical and quantitative descriptive cross-sectional study. Four urban and four rural primary schools were conveniently sampled. Pupils aged 11–14 years (n = 409) were recruited using self-administered structured questionnaire. Data were analyzed using SPSS program v20.0. Results. Out of 409 pupils, most of them had knowledge that dental caries is caused by consumption of sugary foodstuffs (91.4%), toothache is a symptom of dental caries (77.6%), gingivitis is caused by ineffective tooth brushing (92.7%), and gingival bleeding is a sign of gingivitis (85.3%). Most pupils experienced toothache (30.8%); many of them had parents with secondary education and above (35.0%) compared to those with primary education (23.5%). 24.4% experienced gingival bleeding with higher percentages from urban (30.1%) than rural (18.5%) schools. Plastic toothbrush users (95%) overshadowed chewing stick users (24.9%). The use of chewing stick was significantly higher in rural (49%) than in urban (1.9%) schools. Likewise, tooth brushing before bed was significantly higher in rural (33%) than in urban (17.2%) pupils. The use of toothpaste during tooth brushing was significantly higher among urban (91.9%) than among rural (64%) pupils. The prevalence of tongue cleaning was 70.2%, and the differences were significantly higher among pupils who had parents with secondary and higher education in urban schools and among pupils aged 11–12 years in comparison with their counterparts. Conclusions. Most pupils reported cleaning their teeth regularly, mostly using plastic toothbrush rather than chewing stick, using toothpaste, and having adequate knowledge about dental caries and gingival disease, and a quarter of them had suffered from these diseases with evidence of rural-urban disparities. Integration of oral health in school health promotion program and further research on its impact on oral health status are recommended.